2016
DOI: 10.1155/2016/1859321
|View full text |Cite
|
Sign up to set email alerts
|

National Trends of Antiparkinsonism Treatment in Taiwan: 2004–2011

Abstract: Background. Several guidelines for Parkinson's disease (PD) management were recently updated. We examined temporal trends for antiparkinsonism drugs in Taiwan. Methods. Antiparkinsonism prescriptions, including levodopa, ergot/nonergot dopamine agonists (DAs), amantadine, selegiline, entacapone, and anticholinergics, were identified in the Taiwan National Health Insurance Database from 2004 to 2011. Time trend analyses were estimated assuming Poisson distribution. Results. A total of 19,302 PD patients in 2004… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 24 publications
(36 reference statements)
0
19
0
2
Order By: Relevance
“…DA monotherapy in Taiwan represented 2.25% of prescriptions in 2004 and then increased to 4.85% in 2011 in younger patients. Also, the percentage of DA monotherapy prescribed was almost twofold higher compared to the older-aged group 31…”
Section: Discussionmentioning
confidence: 87%
“…DA monotherapy in Taiwan represented 2.25% of prescriptions in 2004 and then increased to 4.85% in 2011 in younger patients. Also, the percentage of DA monotherapy prescribed was almost twofold higher compared to the older-aged group 31…”
Section: Discussionmentioning
confidence: 87%
“…Most available studies on drug-prescribing patterns in PD have been cross-sectional analyses or use the drug tracer methodology, making it difficult to identify changing patterns in PD drug utilization or patient factors that influence the choice of drug [4][5][6]. In studies with longitudinal data, analyses were on patients with a varied duration of illness; thus, were not designed to answer which dopaminergic replacement strategy was preferred by physicians as initial therapy [7,8]. e aim of this study is to compare PD treatment practices by movement disorder (MD) specialists across a decade and to determine the factors that influence drug choice in newly diagnosed drug-naïve PD patients in Singapore.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, including a retrospective database analysis in Taiwan comparing prescribing practices from 2004 to 2011, have demonstrated a trend of increased nonergot dopamine agonist (DA) use in younger aged participants. 3 Recently, however, several studies have been published recognizing impulse control disorders (ICDs) as a side effect of DAs. [4][5][6] In a large cross-sectional study of more than 3,000 participants, it was demonstrated that there was a 2-fold to 3.5-fold increased odds of having an ICD with DA therapy.…”
mentioning
confidence: 99%
“…Previous studies, including a retrospective database analysis in Taiwan comparing prescribing practices from 2004 to 2011, have demonstrated a trend of increased nonergot dopamine agonist (DA) use in younger aged participants . Recently, however, several studies have been published recognizing impulse control disorders (ICDs) as a side effect of DAs .…”
mentioning
confidence: 99%